Use of positive end-expiratory pressure titration and recruitment maneuvers in pediatric intensive care unit - A narrative review - Anil Sachdev; Pradeep Kumar; Mohammed Ashif (Wolters Kluwer Medknow Publications, 2023)
Mechanical ventilation is a lifesaving support for patients suffering with acute respiratory distress syndrome. This modality is likely to cause ventilator-induced lung injury if not used judiciously and appropriately. Lung protective ventilation strategy is routinely practiced in adult and pediatric intensive care units. Positive end-expiratory pressure (PEEP) and recruitment maneuvers (RMs) are used in "Open Lung Ventilation" strategy and to keep the lung open. PEEP is applied to recruit collapsed alveoli to improve oxygenation, compliance, reduce tidal stress, and strain on the lungs and to promote homogenous lung ventilation. There is no agreement on methods to set "Best PEEP" for a particular patient. There are many approaches described in published literature to optimize PEEP. PEEP titration may be done with PEEP/FiO2 grid, targeted compliance, driving pressure, by using pressure-volume curve and stress index. Esophageal manometry and measurement of end-expiratory lung volume may be used if special equipment, machines, and expertise are available. No single method of PEEP titration has been shown to improve outcome. RM is characterised by sudden transient increase in transpulmonary pressure. Different RMs including high-frequency oscillator ventilation and prone position ventilation have been studied in adults and pediatric patients with very conflicting results and inconsistent survival benefits. Serious complications, hemodynamic instability, air leak syndrome, transient, or no improvements in oxygenation are reported. In this narrative review, we have discussed different methods of PEEP titration and RMs and available evidence for each especially in children.